EKSISTENSI HUKUM DALAM IMPLEMENTASI PIDANA MATI TERHADAP KORUPTOR DALAM PERSPEKTIF PEMBAHARUAN HUKUM PIDANA - Mardiman Sane (Law and Communication Journal, 2025)
Indonesia, which is currently in the realm of criminal law reform, cannot be separated from the issue of the death penalty. Of course, this will have an impact in the context of the formation of a new Criminal Code (KUHP) made by the Indonesian people themselves who have long desired it. This writing aims to find out the existence of the death penalty through the development of how the death penalty is regulated in the Criminal Code and in the Draft Criminal Code. The results of the research in this writing are that the death penalty in the Criminal Code has the nature of a principal crime, but in the Draft Criminal Code as a special crime or a crime that is threatened alternatively. That the application of the death penalty for perpetrators of corruption if only examined textually, then the application of the death penalty is contrary to Human Rights as stated in Article 28A paragraph (1), 28I paragraph (1), in conjunction with Article 4 of Law Number 39 of 1999, in conjunction with Article 3 of the Universal Declaration of Human Rights.